Suspended sediments atmospheric deposition and specific transport in hydrographic basins under mining influence in the Poços de Caldas Plateau (MG) - Sardinha, Diego de Souza; Silva, Leonardo Barbosa; Ferreira, Adriano Mota [UNESP]; Menezes, Paulo Henrique Bretanha Junker (Revista Brasileira de Geografia Fisica, 2022)
Poços de Caldas volcanic caldera, a geological formation rich in bauxite, is located in the southern region of Minas Gerais State. Despite its economic and social importance, mining can cause some impacts such as erosion, increased runoff and silting. The present study quantified total suspended solids atmospheric deposition and specific transport in the Gigante and Chapadão Stream hydrographic sub-basins, under mining influence, in Poços de Caldas Plateau (MG). 14-rainwater samples and 26-river water were collected and analyzed. Rain deposition and fluvial transport were 6.00 t/year and 1.47 t/year for Gigante, and 26.65 t/year and 40.64 t/year for Chapadão, respectively. The specific transport in the Gigante (0.40 t/km2/year) and Chapadão (2.49 t/km2/year) have values below other basins in the Plateau region. On the other hand, atmospheric deposition was 1.64 t/km2/year, above other basins in the Plateau region, despite the small numbers of studies. The differences were-1.24 t/km2/year for Gigante and 0.85 t/km2/year for Chapadão, indicating that rainwater contributes with approximately 400% of suspended solids for Gigante and 65% for the Chapadão. Mining activities, employing adequate procedures, with vegetation cover in the main drainage, may be mitigating total suspended solids transport carried by surface runoff. Nevertheless, measures to control air pollution diffuse type and reduce particulate matter can be adopted.
Deposição atmosférica e transporte específico de sedimentos suspensos em bacias hidrográficas sob influência de mineração no Planalto de Poços de Caldas (MG)1
Keywords: Cipó reservoir; defluvium; nitrate; phosphate; sulfate